MENTORING AND TRAINING FISH BREEDING - Fatimah Fatimah; Sugiyanto Sugiyanto; Ary Kurniati (UPPM Poltekkes Kemenkes Semarang, 2017)
The purpose of these activities improve the knowledge and skills of people, especially the breeding of livestock and fish breeding to increase the quality and increase production and be able to compete in the market as well as a means of education. Realization implementation activities in the form of learning, training and mentoring. Stages are conducting learning activities lectures giving the material, strengthening the material with a demonstration and simulation as well as good guidance for implementation in the form of monitoring and evaluation. The target audience of the event is the productive economic business group consists of 25-30 people, which the people of residents who have been focusing on small and independent businesses have both individually and in groups. Delivery of materials, simulations and discussions, delivered with total training hours to 50 hours. Revitalization of land is done by fixing the pool walls were eroded and landslides. Installation waring on pond breeding and nursery grounds. The addition of adequate water filter, the drain water pump to the pool with a filter system, after going through the water inlet filter back to pool. Training and Mentoring fish farming, in the form of breeding carp, catfish and fish, made with fish polyculture system is selected are kept together with other fish, so that the effective time and the results can be harvested alternately.